Pelatihan Fotografi Dan Menulis Cerita Visual Pada Santri SMA Excellent Pesantren Modern Nurul Ikhlas - Alvira, Idea; Hafid, Fauziah Sri Andria; Victory, Well; Nurdiani, Silvana; Ramadan, Rahmad (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the current digital era, photography as a visual communication media has become an important part of human life. Unfortunately, today’s society, especially students, still lacks this knowledge. By holding photography training and writing for students, it is hoped that their hard skills will increase. In this case, the team from ISI Padangpanjang provided photography training and visual story writing at Nurul Ikhlas Excellent High School. This training is provided using the lecture method. After presenting the material, the students take photos with objects of social life in the Islamic boarding school environment. The student's photo work is paired with a visual story in the form of a narrative. As an appreciation for this work, all of the students' works were exhibited in the Islamic boarding school environment. This training succeeded in raising the enthusiasm of the students to develop themselves. Other students who did not take part in the training also hope that in the future they will get the opportunity to receive similar training.